Associations between internet addiction and psychological problems among adolescents: description and possible explanations - Xue, Yaqing; Xue, Benli; Zheng, Xiao; Shi, Lei; Liang, Pengyan; Xiao, Shujuan; Dong, Fang; Zhang, Jiachi; Chen, Yaguang; Liu, Yuxi; Qin, Zuguo; Zhang, Chichen (Frontiers in Psychology, 2023)
Internet addiction (IA) is becoming a significant public health issue that requires urgent attention, especially for adolescents. Previous studies mainly focused on the risk factors of Internet addiction and drawn some conclusions. The purpose of this study is to investigate the Internet addiction status and concurrent psychological problems in adolescent groups, and explore the differences in the relationship between IA and psychological problems in adolescents from gender and grade. A cross-sectional study was conducted among students of junior and senior high school in 21 prefecture-level cities of Guangdong Province. The Young Diagnostic Questionnaire (YDQ) and the validated Chinese version of the Depression Anxiety Stress Scale-21 (DASS-21) were used to assess participants’ Internet addiction and psychological status. The results showed that the prevalence of problematic Internet use (PIU), depression, anxiety, and stress symptoms among adolescents were 16.32%, 30.16%, 35.97% and 18.80% respectively. Although the prevalence of PIU among boys was higher than that of girls (17.89% vs 14.86%, P<0.05), the scores of depression, anxiety and stress among girls in PIU group were significantly higher than those in boys. Similarly, the interaction between grade and Internet addiction was also significant (P<0.05). Although the prevalence of PIU was the highest in grade 9 (17.29%), the adverse effects of Internet addiction on psychological problems were different in different grades. These imply that we should not only consider the high prevalence of PIU among boys and grade 9 students, but also explore the possible negative effects of Internet addiction on the characteristics of different groups. And long-term follow-ups should be included in mental health programs of adolescents to monitor the development of Internet addiction and psychological problems.